Radiological Health Risk Assessment of Naturally Occurring Radionuclides in Road Dusts from Road Consruction Sites In Ijebu-Ode, Ogun State, Nigeria - Oladapo, Francis; Amaju, Robinson (FUDMA Journal of Sciences, 2026)
This study assessed the activity concentrations and radiological health risks associated with naturally occurring radionuclides in road dust samples obtained from road construction sites in Ijebu-Ode, Ogun State, Nigeria. Fifteen soil samples were collected from road construction sites on Ereko and Talbort Streets, Ijebu-Ode. The soil samples were air-dried, homogenised, sieved, treated and analysed using gamma spectrometry at the University of Ibadan, for the concentrations of Uranium-238, Thorium-232, and Potassium-40. Descriptive statistics, Pearson correlation, a two-way analysis of Variance (ANOVA), hierarchical clustering, and principal component analysis (PCA) were employed for statistical evaluation of the data. The mean activity concentrations of Uranium-238, thorium-232, and Potassium-40 were 8.36+-1.81, 15.17+-1.53, and 370.20+-47.44 Bq/kg. Potassium-40 experienced the highest concentration across all sampling locations. The two-way ANOVA revealed a significant difference among the radionuclide type (p<0.05), whereas spatial variation among sampling locations was not statistically significant. A strong positive correlation (r=0.976) was observed between the absorbed dose rate and radium equivalent activity. The calculated absorbed dose rate, annual effective dose equivalent, radium equivalent activity, external hazard index, internal hazard index, and excessive lifetime cancer risk were below internationally recommended safety limits. PCA and hierarchical clustering further indicated relatively homogenous radiological characteristics across the study area, with slight variations associated with primarily with potassium-40 distribution. The findings indicate that the investigated road dust samples do not pose significant radiological health hazards to construction workers or residents within the study area.